Comparison between two on-demand protocol and one demand for mobile ad hoc network - Mohamed El-marghine Mana Gannan; Ahmed H. Elhetsh; Abdulmunem k. Assyeh (Surman Journal of Science and Technology, 2024)
An ad-hoc network is a collection of wireless mobile nodes dynamically forming a temporary network without the use of any existing network infrastructure or centralized administration. A number of routing protocols likes Dynamic Source Routing (DSR), Ad Hoc on-Demand Distance Vector Routing (AODV) and Destination-Sequenced Distance-Vector (DSDV) Routing Algorithm has been implemented. In this paper an attempt has been made to compare the performance of two prominent on-demand reactive routing protocols for mobile ad-hoc networks: DSR and AODV, along with the traditional proactive DSDV protocol for different simulation times and connectivity sources using ns-2 simulator. The performance differentials are analyzed using varying network load, mobility, simulation times, connectivity sources and network size. The selected measuring criteria used to evaluate the routing protocols are: packet delivery ratio, average end-to-end delay of data packets, normalized routing load, routing packet overhead. The On-demand protocols, AODV and DSR perform better than the table-driven DSDV protocol. Although DSR and AODV share similar on-demand behavior, the differences in the protocol mechanics can lead to significant performance differentials.